Pengaruh Perbedaan Suhu Pengeringan Menggunakan Tray Dryer terhadap Karakteristik Fisik dan Kimia Cabai Rawit (Capsicum frutescens L.) - Susilawati Susilawati; Devi Tanggasari (Department of Pharmacy, Bumigora University, 2023)
Cayenne pepper (Capsicum frutescens L.) is a potential vegetable crop that has high economic value and has the potential to continue to be developed, but cayenne pepper is a type of fruit that is easily damaged, therefore proper post-harvest handling is needed, one of which is drying. The purpose of this study was to determine the effect of different drying temperatures on physical analysis (weight loss) and chemical analysis (moisture content, vitamin C and capsaicin content). The dryer used in this study was a tray dryer. The experimental design used was a one-factor Completely Randomized Design (CRD) with 3 treatments. The temperatures used in this study were 40, 50, and 55°C. Based on the results of the study, it was found that the best decrease in weight loss in drying cayenne pepper was at 55°C with a decrease in weight loss of 62.67%. The best decrease in water content for drying cayenne pepper was at 55°C with a total moisture content of 50.3%. The best vitamin C content was found at 45°C, which was 0.65%, and the best capsaicin content for drying cayenne pepper was found at 45°C, which was 244.4702 ppm with an SHU level of 730.776.